1984
DOI: 10.1038/309030a0
|View full text |Cite
|
Sign up to set email alerts
|

Cell attachment activity of fibronectin can be duplicated by small synthetic fragments of the molecule

Abstract: The ability of fibronectin to bind cells can be accounted for by the tetrapeptide L-arginyl-glycyl-L-aspartyl-L-serine, a sequence which is part of the cell attachment domain of fibronectin and present in at least five other proteins. This tetrapeptide may constitute a cellular recognition determinant common to several proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
2,044
4
27

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,426 publications
(2,143 citation statements)
references
References 32 publications
37
2,044
4
27
Order By: Relevance
“…5,17 Therefore, the investigation of entire peptide chains in contact with inorganic surfaces is a critical component in advancing our understanding. 26 The tripeptide motif RGD and its interaction with titania surfaces has been of particular interest, [27][28][29][30][31][32][33] while others have sought to isolate and identify TiO2-binding peptides using biocombinatorial techniques to gain a deeper understanding of which peptide characteristics can confer strong titania-binding affinity. 32,[34][35][36][37] A crucial next step in advancing our understanding is the careful characterization of the adsorption of materials-binding peptides at aqueous titania interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…5,17 Therefore, the investigation of entire peptide chains in contact with inorganic surfaces is a critical component in advancing our understanding. 26 The tripeptide motif RGD and its interaction with titania surfaces has been of particular interest, [27][28][29][30][31][32][33] while others have sought to isolate and identify TiO2-binding peptides using biocombinatorial techniques to gain a deeper understanding of which peptide characteristics can confer strong titania-binding affinity. 32,[34][35][36][37] A crucial next step in advancing our understanding is the careful characterization of the adsorption of materials-binding peptides at aqueous titania interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The Arg-Gly-Asp (RGD) motif was originally identified as the site within fibronectin that mediates cell attachment [1]. Soon thereafter it was demonstrated that several other extracellular proteins containing an RGD motif play a role in cell adhesion processes in many different mammalian tissues via their RGD functional site.…”
Section: Introductionmentioning
confidence: 99%
“…26 In attempts to address these issues, several laboratories have developed compliant polyurethane composites. [27][28][29] In the approach presented here, we focus on elastin, which forms a crosslinked network in the arterial wall 30 and which, along with collagen, imparts elasticity and resiliency to the M-MASMTGGQQMG-HHHHHHH-DDDDK(LD-YAVTGRGDSPASSKPIA((VPGIG) 2 VPGKG(VPGIG) 2 ) 4 VP) 3 [41][42][43] this sequence serves as a ligand for the α v β 3 and α 5 β 1 integrins. 44,45 aECM 2 is a negative control for aECM 1, in which the sequence of the RGD cellbinding domain has been scrambled.…”
mentioning
confidence: 99%